1999
DOI: 10.1021/la981738l
|View full text |Cite
|
Sign up to set email alerts
|

An Atomic Force Microscopy Study of Ordered Molecular Assemblies and Concentric Ring Patterns from Evaporating Droplets of Collagen Solutions

Abstract: Ordered molecular assemblies spontaneously appeared from evaporating droplets of collagen solutions on glass substrates. Nanoscopic structures of the assemblies were examined using an atomic force microscope; well aligned collagen molecules oriented their ends toward the assembly surface and formed layered structures for concentrations >0.05 mg/mL, while the molecules, mostly curved, lay for concentrations <0.005 mg/mL. The layers exhibited a variety of morphological forms (e.g., regular, undulated, and rolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
40
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 31 publications
6
40
1
Order By: Relevance
“…The pure type I collagen (Fig. 5a) exhibit typical fibrillar structure on the mica substrate where many curved molecules or microfibrils lie and are overlapped with one another, similar to previous reports [41,42]. While in the presence of procyanidin (Fig.…”
Section: Influence Of Procyanidin On the Structure Of Collagensupporting
confidence: 87%
“…The pure type I collagen (Fig. 5a) exhibit typical fibrillar structure on the mica substrate where many curved molecules or microfibrils lie and are overlapped with one another, similar to previous reports [41,42]. While in the presence of procyanidin (Fig.…”
Section: Influence Of Procyanidin On the Structure Of Collagensupporting
confidence: 87%
“…In 1992, Chernoff and Chernoff 23 already showed the effect of pH on the formation of collagen fibrils on adsorption. Later, Mertig and colleagues 24 produced collagen layers with different geometries on the basis of dewetting, whereas Maeda 25 showed that ordered collagen structures could be formed on evaporation of concentrated collagen solutions. In our laboratory, the factors affecting the morphology and the physicochemical properties of adsorbed collagen layers have been thoroughly studied in the last few years and reviewed recently.…”
Section: Fibroblastsmentioning
confidence: 99%
“…Collagen is utilized for coating PVDF substrates. Collagen exhibits biodegradability, has excellent biocompatibility, as well as safe to use in medical field due to its biological characteristics (Maeda, 1999).…”
Section: Introductionmentioning
confidence: 99%